A new portfolio formation approach to mispricing of marketing performance indicators with an application to customer satisfaction - David R. Bell; Olivier Ledoit; Michael Wolf (University of Zurich, Department of Economics, 2013)
The mispricing of marketing performance indicators (such as brand equity, churn, and customer satisfaction) is an important element of arguments in favor of the financial value of marketing investments. Evidence for mispricing can be assessed by examining whether or not portfolios composed of firms that load highly on marketing performance indicators deliver excess returns. Unfortunately, extant portfolio formation methods that require the use of a risk model are open to the criticism of time-varying risk factor loadings due to the changing composition of the portfolio over time. This is a serious critique, as the direction of the induced bias is unknown. As an alternative, we propose a new method and construct portfolios that are neutral with respect to the desired risk factors a priori. Consequently, no risk model is needed when analyzing the observed returns of our portfolios. We apply our method to a frequently studied marketing performance indicator, customer satisfaction. Using various ways of measuring customer satisfaction, we do not find any convincing evidence that portfolios that load on high customer satisfaction lead to abnormal returns.
Keywords: G11; G12; 330; Customer satisfaction; financial performance; long-short portfolio; mispricing